1995
DOI: 10.1080/01635589509514415
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene is a more potent inhibitor of human cancer cell proliferation than either α‐carotene or β‐carotene

Abstract: The antiproliferative properties of lycopene, the major tomato carotenoid, were compared with those of alpha- and beta-carotene. Lycopene, delivered in cell culture medium from stock solutions in tetrahydrofuran, strongly inhibited proliferation of endometrial (Ishikawa), mammary (MCF-7), and lung (NCI-H226) human cancer cells with half-maximal inhibitory concentration of 1-2 microM; alpha- and beta-carotene were far less effective inhibitors. For example, in Ishikawa cells, a 4-fold higher concentration of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
240
0
11

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(262 citation statements)
references
References 22 publications
8
240
0
11
Order By: Relevance
“…A number of studies have suggested that lycopene's effect on chronic disease may be mediated through effects on IGF-1. One study (Levy et al, 1995) compared the effect of lycopene on cancer cell proliferation with a-carotene or b-carotene. Lycopene was much more effective than the other two compounds in inhibiting human breast, endometrial and lung cancer IGF-1-stimulated cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have suggested that lycopene's effect on chronic disease may be mediated through effects on IGF-1. One study (Levy et al, 1995) compared the effect of lycopene on cancer cell proliferation with a-carotene or b-carotene. Lycopene was much more effective than the other two compounds in inhibiting human breast, endometrial and lung cancer IGF-1-stimulated cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed circulating IGF-1 to be associated with increased risk of prostate and pre-menopausal breast cancer (Renehan et al, 2004). A number of studies have suggested a link between lycopene and IGF-1-stimulated cell proliferation in vitro (Levy et al, 1995;Karas et al, 2000), and an inverse association has been demonstrated between cooked tomato consumption and circulating IGF-1 concentrations in vivo (Mucci et al, 2001;Gunnell et al, 2003). Other studies have, however, failed to show an association between circulating IGF-1 and lycopene concentrations (Graydon et al, 2003;Vrieling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In three of these studies, higher intake of cooked or processed tomatoes or lycopene was associated with either lower IGF-I levels [14], higher IGFBP-3 levels [22], or a lower IGF-I/IGFBP-3 molar ratio [18]. Two in vitro studies have shown that lycopene can inhibit IGF-I-stimulated growth of endometrium and mammary cancer cell lines [34,35]. In these studies, lycopene reduced IGF-I receptor signaling, and increased levels of membrane-associated IGFBPs [35].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, results differed for pre-and postmenopausal women [31], which suggests that the effects of phytoestrogens on the IGF system components may be dependent on endogenous estradiol concentrations. Lycopene is an anti-oxidant mainly found in cooked or processed tomatoes, and has been suggested to interfere with IGF signaling in experimental studies [34][35][36]. Also in cross-sectional studies lycopene [22] or cooked or processed tomatoes [14,18] were associated with IGF-I or IGFBP-3.…”
Section: Introductionmentioning
confidence: 99%
“…53 These include an upregulation in intercellular gap junctions, 54 an increase in cellular differentiation 55 and alterations in phosphorylation of some regulatory proteins. 56 Little is known regarding the role or indeed importance of these effects in vivo, however, lycopene has been demonstrated to be significantly more efficient than any carotene in inhibiting insulin-like growth factor type 1 (IGF1) induced proliferation of a number of tumour cell lines 57 and decrease the occurrence of both spontaneous and chemically induced mammary tumours in animal models. 58,59 In prostate cancer, in particular, a study has demonstrated inhibition of cell line proliferation in the presence of physiological concentrations of lycopene in combination with alpha-tocopherol.…”
Section: Lycopene and The Biology Of Cancermentioning
confidence: 99%